The impact of multiple interventions to reduce household exposure to second-hand tobacco smoke among women: a cluster randomized controlled trial in Kalutara district, Sri Lanka - A. M. A. A. P. Alagiyawanna; N. Rajapaksa -Hewageegana; N. Gunawardena (BMC, 2017)
Abstract Background Second-hand smoke (SHS) in households remains a serious public health problem in Sri Lanka, partly due to a lack of voluntary prohibitions of tobacco smoking inside houses. Women are especially at risk of being exposed. Effective community based interventions to reduce the SHS in households targeting women is scarce. The objective of this study was to examine the impact of a multi-component intervention on household SHS exposure among Sri Lankan women. Methods Thirty clusters of 25 women (aged 18-65) from 750 households were randomized into the intervention and control groups. Women in the intervention group were exposed to activities which focused on improving knowledge on the health effects of SHS, attitudes towards SHS exposure, right to a smoke-free living and women empowerment against smoking. The duration of the intervention was six months. The comparison group received no intervention. The primary outcome of interest was self-reported SHS exposure in the household within 7 days prior to data collection. The secondary outcomes were exposure in the past 30 days, knowledge of the health risks of exposure, attitudes towards exposure, right to smoke-free living, women empowerment against smoking, and smoking inside the homes. Results Final assessment was in 329 (89.6%) in the intervention group and 309 (85.8%) in the comparison group. Following the intervention, significantly lower proportion of women in the intervention group as compared to the control group reported SHS exposure in their households within 7-days (9.2% vs. 15.3%, p = 0.02) and 30-days (13.6% vs. 21.6%, p = 0.008) prior to the post survey. As compared to the control group, significantly higher median scores were observed in the intervention group on the knowledge of the health risks of exposure to SHS (p < 0.001), attitudes on exposure to SHS (p = 0.004), right to smoke free living (p = 0.001) and women empowerment (p < 0.001). Conclusion Multi-component intervention activities were effective in reducing household exposure to SHS among women. Trial registration Sri Lanka Clinical Trials Registry SLCTR/2014/033.